Penerapan Analisis Studi Kelayakan Bisnis Dilihat Dari Aspek Pemasaran Pada Praktik Pemasaran E-Commerce “Stick Singkong Krispy” - Rita Sri Silvia Pamuji; Dede Susilo HSBW; Muhamad Nizar Pramudita; Enggun Yoga Nugraha (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
Entrepreneurial business opportunities in the food sector are wide open because all humans definitely need food with this promising opportunity, so we plan to design a culinary business "Crispy Cassava Stick". This study uses a research approach, where researchers collect data in five ways, namely: navigator, focus group, survey, behavioral data, and experiment. Search results c during the soft opening in three days sold up to 65 pieces/day which was originally expected to be only 50 pieces/day. Delivery sales cover all areas of Majalengka Regency, such as Cigasong, Kadipaten, Kasokandel, Banjaran and Sukahaji Sindangkasih, Jatiwangi Bantaragung and other areas around Majalengka Regency.So expected in the grand opening period, sales of "Crispy Cassava Stick" using continuous homogenization selected by management α 0.20 Quantity: New forecast (for demand in the grand opening period) 50 + 0.2 (50-65) 80 pieces. He concluded that online commerce or known as e-commerce has an impact on the existence of MSMEs in the food industry in Magalingka in terms of income and number of consumers. As a form of embedding marketing practices through e-commerce,  promotional strategies that can be done or commonly referred to as a promotional mix with advertising or sales promotion through social media or E-commerce and personal sales or can be done with digital marketing through the use of technology in the 5.0 era that collaborates machines and humans or commonly called artificial intelligence (artificial intelligence)). Even promotional activities that can be done today can involve infulencer as a promotional medium which is often called advocacy.